ROLE COMMUNITY-BASED DISASTER MANAGEMENT SYSTEM: SYSTEMATIC REVIEW - Suhari Suhari; Dwi Okta Pebriyanti; R Endro Sulistyono; Primasari Mahardika Rahmawati (UPT Penerbitan Universitas Jember, 2023)
Background: Community based disaster risk management (CBDRM) is used to reduce disaster risk and increase community resilience to disasters that occur. Community-based disaster risk management is one of the main trends of international disaster prevention and reduction, which was firstly established in the UK in the late 1980s and has since been widely valued and applied by international, national, and local organizations. This study was to access the individual disaster preparedness of villagers in a northwestern rural community and examine the determinants of their individual disaster preparedness across multiple dimensions: place, individual sociodemographic factors, family socioeconomic status, hazard adaptation, community and environmental influences. Methods: This article was obtained from 2018 to 2023. This research is a study using the Systematic Literature Review method. The search strategy used in this literature review is to use 4 databases, including Elsevier, Science Direct, Pubmed, Plos One, and Grey Literature. The interactions between the different determinants will be discussed. The design used in this study was a systematic review using the PRISMA 2009 flowchart, namely selecting articles that did not comply with the criteria for inclusion, screening, eligibility, and downloading of articles. Results: A total of 10 articles were analyzed, this study reveal that community-based risk management can reduce disaster risk and increase community resilience to disasters that occur as well as increase community capacity to prepare themselves and increase community knowledge about disasters. Conclusions: Communities need to be empowered in the role of disaster management in rural areas. Keywords: Community, Role, Disaster Risk Management, Rural